2023
DOI: 10.1002/adsc.202300456
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Sulfonyl Dibenzofused Medium‐Size Oxacycles via Bi(OTf)3‐Catalyzed Friedel‐Crafts‐Type Annulation

Abstract: Herein, Bi(OTf)3‐catalyzed Friedel‐Crafts‐type annulation of sulfonyl o‐hydroxyacetophenones with benzofused cycloethers is described. This single‐step strategy provides a variety of functionalized dibenzofused medium‐size (9–12) oxacycles through the formation of carbon‐carbon and carbon‐oxygen single bonds. Further, the oxidative application of target oxacycles was investigated. The chemical structures of the key products were determined based on the single‐crystal X‐ray analysis. In the overall process, wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…The results indicated that the refluxing temperature (101 °C) was suitable to enhance the yield. According to our previous reports on the bismuth-catalyzed annulations, 15 BiCl 3 was screened next. No obvious improvement in the isolated yield of 6a was detected (entry 4, 75%).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the refluxing temperature (101 °C) was suitable to enhance the yield. According to our previous reports on the bismuth-catalyzed annulations, 15 BiCl 3 was screened next. No obvious improvement in the isolated yield of 6a was detected (entry 4, 75%).…”
Section: Resultsmentioning
confidence: 99%